2015
DOI: 10.1136/archdischild-2015-308464
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of flow driver and bubble continuous positive airway pressure in preterm infants in a resource-limited setting

Abstract: ISRCTN22578364.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Using an underwater seal to generate the pressure, or “Bubble CPAP,” generates small fluctuations around the set pressure which some believe offers additional advantage [93]. Using a flow driver to generate CPAP has the theoretical advantage of offloading expiratory work of breathing (the Coanda effect), although no important clinical differences have been shown among devices used to deliver CPAP, but the simplicity of bubble CPAP systems allows their use in low-income settings [94]. Trials comparing interfaces show no differences between nasal prongs and short pharyngeal tubes for initial stabilisation in the delivery room [50], but for prolonged use nasal masks may be most effective [95].…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…Using an underwater seal to generate the pressure, or “Bubble CPAP,” generates small fluctuations around the set pressure which some believe offers additional advantage [93]. Using a flow driver to generate CPAP has the theoretical advantage of offloading expiratory work of breathing (the Coanda effect), although no important clinical differences have been shown among devices used to deliver CPAP, but the simplicity of bubble CPAP systems allows their use in low-income settings [94]. Trials comparing interfaces show no differences between nasal prongs and short pharyngeal tubes for initial stabilisation in the delivery room [50], but for prolonged use nasal masks may be most effective [95].…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…We performed full-text review of 68 studies of which 47 were excluded with valid reasons (figure 1). A total of 21 studies9 11–16 19–22 28–37 were included (study characteristics shown in online supplementary file 2), of which 199 11–16 19–22 28–30 32–36 were included in meta-analyses for all outcomes and 129 12 15 16 19–21 28 30 34–36 were included in meta-analysis for the primary outcome. Of 21 studies, one article in Persian and one written in Portuguese were translated with the help of Persian and Portugal colleagues at our institution.…”
Section: Resultsmentioning
confidence: 99%
“…Of 21 studies, one article in Persian and one written in Portuguese were translated with the help of Persian and Portugal colleagues at our institution. Of the 19 studies included in the meta-analyses for all outcomes, 5 had high risk,20 22 28 30 32 8 had an unclear risk11 14 16 19 21 29 33 34 and 6 had low risk of bias9 12 13 15 35 36 as shown in figures 2 and 3. In all studies, blinding of participants and healthcare personnel could not be performed due to the nature of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations